Event-Related Theta Power during Lexical-Semantic Retrieval and Decision Conflict is Modulated by Alcohol Intoxication: Anatomically Constrained MEG - Marinkovic, Ksenija; Rosen, Burke Q.; Cox, Brendan; Kovacevic, Sanja (Frontiers in Psychology, 2012)
Language processing is commonly characterized by an event-related increase in theta power (4-7 Hz) in scalp EEG. Oscillatory brain dynamics underlying alcohol's effects on language are poorly understood despite impairments on verbal tasks. To investigate how moderate alcohol intoxication modulates event-related theta activity during visual word processing, healthy social drinkers (N=22, 11 females) participated in both alcohol (0.6 g/kg ethanol for men, 0.55 g/kg for women) and placebo conditions in a counterbalanced design. They performed a double-duty lexical decision task as they detected real words among nonwords. An additional requirement to respond to all words that also referred to animals induced response conflict. High density whole head MEG signals and midline scalp EEG data were decomposed for each trial with Morlet wavelets. Each person’s reconstructed cortical surface was used to constrain noise-normalized distributed minimum norm inverse solutions for theta frequencies. Alcohol intoxication increased reaction time and marginally affected accuracy. The overall spatiotemporal pattern is consistent with the left-lateralized fronto-temporal activation observed in language studies applying time domain analysis. Event-related theta power was sensitive to the two functions manipulated by the task. First, theta estimated to the left-lateralized fronto-temporal areas reflected lexical-semantic retrieval, indicating that this measure is well suited for investigating the neural basis of language functions. While alcohol attenuated theta power overall, it was particularly deleterious to semantic retrieval since it reduced theta to real words but not pseudowords. Second, a highly overlapping prefrontal network comprising lateral prefrontal and anterior cingulate cortex was sensitive to decision conflict and was also affected by intoxication, in agreement with previous studies indicating that executive functions are especially vulnerable to alcohol intoxication.